Conversations with employers: Exploring graduate employability in Bangladesh - Matin, Imran; Ali, Tariq; Wiebe, Paul (2022)
The Bangladeshi graduate labour market is going through rapid and dramatic changes. The increasing importance of the private sector coupled with the intensifying forces of globalization has considerably changed employers’ needs regarding graduate employment. The research focuses on employers’ perspective in this rapidly changing graduate labour market. It specifically addresses two questions: What are the generic attributes that employers look for? And how do employers find individuals with these attributes? In order to answer these questions, we interviewed a range of employers. However, the paper focused on sectors that are desirable for BRAC University students. The major finding of this research is that the problem of employability is best understood in terms of the linkages between employability attributes, rather than the employability attributes per se. This is because the employability attributes are abstractions that function to describe a composite individual who can add value to an organisation. Skills are therefore not discrete and mutually exclusive categories and the employable graduate is more than the linear sum of employability attributes. The paper concluded that course design, pedagogy, the classroom environment, the reward system, the inclusiveness of the University environment, its regulation and its engagements with the wider social and political landscape, both local and global—and many more will all be important variables that will shape the agenda of enhancing graduate employability.